2016
DOI: 10.1111/jce.12907
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relation Between Left Atrial Anatomical Contact Areas and Circular Activation in Persistent Atrial Fibrillation

Abstract: External anatomical structures contacting the LA may be related to unique conduction properties in diseased myocardium necessary for PsAF maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…[12][13][14][15][16][17][18]20 Fibrotic remodeling tissue acts as an AF substrate because it exhibits slow conduction and short action potential duration, which facilitates reentry. 10,11 Recently, we reported that LVZs are highly coincident with atrial areas in contact with external structures, such as the aorta and vertebrae, and those areas frequently have an electrical circular activation with higher dominant frequencies during AF, 24 suggesting that LVZ areas are associated with unique conduction properties necessary to maintain the AF.…”
Section: Etiology and Role Of The Lvzmentioning
confidence: 99%
“…[12][13][14][15][16][17][18]20 Fibrotic remodeling tissue acts as an AF substrate because it exhibits slow conduction and short action potential duration, which facilitates reentry. 10,11 Recently, we reported that LVZs are highly coincident with atrial areas in contact with external structures, such as the aorta and vertebrae, and those areas frequently have an electrical circular activation with higher dominant frequencies during AF, 24 suggesting that LVZ areas are associated with unique conduction properties necessary to maintain the AF.…”
Section: Etiology and Role Of The Lvzmentioning
confidence: 99%
“…Recent studies employed using high‐density mapping have demonstrated that those sites with more CFEs and faster activation rates, typically targeted during PsAF ablation, are predominantly located in areas with less or minimal fibrosis, and our LVZ targeted ablation, including CoA regions, may eliminate more upstream electrical fibrillatory sources within the damaged atrial tissue. Further, we recently reported that LVZs including CoA regions frequently have an electrical circular activation with higher dominant frequencies during AF . Thus, these findings suggested a mechanistic role of low voltage regions for yielding fractionated electrograms around scarred atrial tissue, which is related with the maintenance of PsAF.…”
Section: Discussionmentioning
confidence: 71%
“…However, locating and identifying these drivers during ablation procedures remains challenging. Recently, atrial fibrosis and its border zones have been recognized as an important substrate of focal and reentrant activity in PsAF patients . Low‐voltage electrograms are mainly due to atrial fibrosis, and imaging techniques such as delayed enhancement MRI could potentially detect the extent of the atrial fibrosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the high‐DF sites were closely related to LVAs in nonparoxysmal AF. LVAs are known to be associated with the electrophysiological effects of an altered conduction velocity, heterogeneous refractoriness, and rapid repetitive activity . Ablation of sites harboring distinct regional electrogram characteristics within/in the vicinity of low‐voltage areas in addition to PVI is more effective than conventional PVI only strategy for persistent AF .…”
Section: Discussionmentioning
confidence: 99%